2009
DOI: 10.1016/j.jasms.2008.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry analysis of photo-induced methionine oxidation of a recombinant human monoclonal antibody

Abstract: Oxidation of methionine (Met) residues of a recombinant fully human monoclonal antibody after exposure to light was investigated and compared with chemically induced oxidation using tert-butyl-hydroperoxide (tBHP). Met256 and Met432 in the Fc region in the samples exposed to light or incubated with tBHP were oxidized. The Fc mass spectra of the antibody exposed to light showed mainly peaks with a molecular weight (MW) increase of 32 Da, however the sample treated with tBHP showed peaks with increase of only 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 13 publications
(21 reference statements)
3
32
0
Order By: Relevance
“…30 For comparison, the light-induced cleavage of glutathione disulfide led predominantly to thiyl radicals. 30 It is well documented that radical mediated damage to proteins may lead to a variety of potentially negative consequences such as fragmentation 23,38 , aggregation 25,38,39 , oxidation [40][41][42][43] , changes to surface hydrophobicity, conformational changes 39 and even denaturation. 38,39 It may also ultimately result in the loss of activity or simply generate new reactive species propagating the radical reactions.…”
Section: Chemistry Of Photooxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…30 For comparison, the light-induced cleavage of glutathione disulfide led predominantly to thiyl radicals. 30 It is well documented that radical mediated damage to proteins may lead to a variety of potentially negative consequences such as fragmentation 23,38 , aggregation 25,38,39 , oxidation [40][41][42][43] , changes to surface hydrophobicity, conformational changes 39 and even denaturation. 38,39 It may also ultimately result in the loss of activity or simply generate new reactive species propagating the radical reactions.…”
Section: Chemistry Of Photooxidationmentioning
confidence: 99%
“…25,38,[41][42][43] Common to all of these studies was photodegradation resulting in the oxidation of tryptophan 38,43 and methionine 38,41,42 with differences noted in specific regions of each antibody. Qi et al observed substantial oxidation of light chain Trp94 in the CDR resulting in multiple oxidation products along with secondary oxidation of Met261, Met437 and His294 of the heavy chain.…”
Section: Prior Work On Protein Photodegradationmentioning
confidence: 99%
“…In addition, this method may help to identify peaks eluting from SEC column directly. (J Am Soc Mass Spectrom 2009, 20, 2258 -2264) © 2009 Published by Elsevier Inc. on behalf of American Society for Mass Spectrometry M ass spectrometry is one of the most indispensable techniques for the characterization of recombinant monoclonal antibodies because most of the modifications that result in heterogeneity and degradation are involved in molecular weight differences [1,2]. Various modifications are determined by analyzing recombinant monoclonal antibodies at different levels, depending on the molecular weight differences of the modifications.…”
mentioning
confidence: 99%
“…Various modifications are determined by analyzing recombinant monoclonal antibodies at different levels, depending on the molecular weight differences of the modifications. Modifications, such as N-terminal glutamine and glutamate cyclization [3][4][5][6][7][8][9], different types of the conserved N-linked oligosaccharides [5,[7][8][9][10][11][12][13], amino acid truncation and insertion [8,11], cysteinylation [14], C-terminal lysine processing [5,7,11,15,16], fragmentation [12,15,17], glycation [18], oxidation [19,20], and nitration [21] can be directly determined by measurements of the molecular weights of intact antibodies, antibody light chain and heavy chain, and Fab and Fc fragments after papain or lys-C digestion [14]. On the other hand, analysis at the peptide level is normally required to determine the sites of modifications and modifications with small molecular weight differences, such as deamidation [22,23] and amidation [11], which results in a molecular weight difference of only 1 Da.…”
mentioning
confidence: 99%
“…In the 3-dimensional structure of a recombinant mAb, 2 methionine residues close to the C H 2À ÀC H 3 interface were found to be easily oxidized. 51,53 Changes in the oxidation status of a mAb can affect its biological function. 32 Previous studies have shown that peroxide-induced oxidation at methionine residues can significantly decrease the binding affinity of the human IgG 1 to Fc receptors.…”
Section: Discussionmentioning
confidence: 99%